1996
DOI: 10.1037/0022-3514.71.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Processing goals, task interest, and the mood–performance relationship: A mediational analysis.

Abstract: The authors examined the role of intrinsic interest in mediating the relationship among mood, processing goals, and task performance. Participants in induced happy, neutral, or sad moods generated similarities and differences between TV shows using performance-based, enjoyment-based, or no stop rule (cf. L.L. Martin, D.W. Ward, J.W. Achee, & R.S. Wyer, 1993). Pretask interest and both quantitative (time spent, number generated) and qualitative (creativity) performance were assessed. Happy participants spent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 35 publications
8
151
2
4
Order By: Relevance
“…For example, in the helping literature, experimental inductions of positive affect produce increased prosocial behavior, whereas inductions of negative affect do not necessarily decrease helping (e.g., Aderman, 1972;Berkowitz, 1987;Isen & Levin, 1972;Rosenhan et al, 1974). Regarding social interactions (e.g., Cunningham, 1988aCunningham, , 1988b, creativity (e.g., Hirt et al, 1996;Richards, 1994), and evaluations of strangers (e.g., Baron, 1987Baron, , 1993, it appears that positive mood inductions do not produce symmetrical effects. Experimental laboratory research-for example, on helping, creativity, and task performance-also often includes neutral mood conditions, which do not parallel the effects of happy mood (e.g., Berkowitz, 1987;Cunningham, 1988a;Estrada et al, 1994;Isen, 1970Isen, , 1993Isen et al, 1985;Rosenhan et al, 1974).…”
Section: Causality and Possible Third Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the helping literature, experimental inductions of positive affect produce increased prosocial behavior, whereas inductions of negative affect do not necessarily decrease helping (e.g., Aderman, 1972;Berkowitz, 1987;Isen & Levin, 1972;Rosenhan et al, 1974). Regarding social interactions (e.g., Cunningham, 1988aCunningham, , 1988b, creativity (e.g., Hirt et al, 1996;Richards, 1994), and evaluations of strangers (e.g., Baron, 1987Baron, , 1993, it appears that positive mood inductions do not produce symmetrical effects. Experimental laboratory research-for example, on helping, creativity, and task performance-also often includes neutral mood conditions, which do not parallel the effects of happy mood (e.g., Berkowitz, 1987;Cunningham, 1988a;Estrada et al, 1994;Isen, 1970Isen, , 1993Isen et al, 1985;Rosenhan et al, 1974).…”
Section: Causality and Possible Third Variablesmentioning
confidence: 99%
“…Laboratory studies have shown that induced happy moods lead participants to derive greater enjoyment from whatever task they are instructed to perform. For example, individuals in an induced positive mood are more likely to enjoy category-sorting tasks (Hirt, Melton, McDonald, & Harackiewicz, 1996;Murray, Sujan, Hirt, & Sujan, 1990), and groups put in a positive mood are more likely to take pleasure in a group negotiation task (Carnevale & Isen, 1986).…”
Section: Enjoyment Of Activities and Social Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Happiness alone is associated with both impaired and enhanced judgments, depending in large part on the type of task involved. Hirt, Melton, McDonald, and Harackiewicz (1996) suggested that positive mood may enhance performance on creativity tasks yet impair performance on tasks requiring more detailed, systematic processing. In support of this distinction, positive mood reliably leads to more creativity in problem solving (e.g., Estrada, Young, & Isen, 1994;Greene & Noice, 1988;Isen, Daubman & Nowicki, 1987;Isen, Johnson, Mertz, & Robinson, 1985), improved integration of available information (e.g., Estrada, Isen, & Young, 1997), and more flexible classification of material (e.g., Isen & Daubman, 1984;Isen, Niedenthal, & Cantor, 1992;Kahn & Isen, 1993).…”
Section: Processing Effects Of Transient and Enduring Affectmentioning
confidence: 99%
“…Although a more standardized measure of fluency might have resulted in greater precision, such a measure would have altered the dynamics of the interaction, reducing external validity. It was important that the measure of fluency be embedded in, not independent of, the situation in which the other measures were taken, because research suggests that situational variation in emotions affects situational variation in cognitive performance (Hirt, Melton, McDonald, & Harackiewicz, 1996). Other researchers have discussed what constitutes valid and authentic assessment of reading ability, with some suggesting that children be assessed while reading connected text from books that are likely to be found in their school (Mathes & Torgesen, 2000;Taylor, Anderson, Au, & Raphael, 2000).…”
Section: Fluency Measuresmentioning
confidence: 99%